2002
DOI: 10.1111/j.1939-1676.2002.tb02382.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glucose Dosage on Interpretation of Intravenous Glucose Tolerance Tests in Lean and Obese Cats

Abstract: Intravenous glucose tolerance tests (IVGTTs) are used in cats and other species to assess insulin sensitivity. Several dosages have been reported but the dosage that maximally stimulates insulin secretion in cats has not been determined nor has it been compared in lean and obese animals. IVGTTs were performed in 4 lean and 4 obese spayed female cats with 5 glucose dosages: 0.3 (A), 0.5 (B), 0.8 (C), 1.0 (D), and 1.3 (E) g/kg body weight (BW). Each cat received each dosage in a random design. The glucose dispos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…It is known that dogs with chronic obesity may show increased cholesterol and triglycerides (Jeusette et al 2005) and diabetes mellitus characterized by increased blood glucose (Hoenig et al 2002, Kim et al 2003. The highly caloric diet induces insulin resistance and decreased insulin ability to transport glucose into peripheral tissue (Kim et al 2003), leading to an increase in insulin secretion (Verwaerde et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that dogs with chronic obesity may show increased cholesterol and triglycerides (Jeusette et al 2005) and diabetes mellitus characterized by increased blood glucose (Hoenig et al 2002, Kim et al 2003. The highly caloric diet induces insulin resistance and decreased insulin ability to transport glucose into peripheral tissue (Kim et al 2003), leading to an increase in insulin secretion (Verwaerde et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…In the domestic cat, substantial elevations in blood glucose are achieved during challenge tests, such as the intravenous glucose tolerance test, due to the rapid injection of large amounts of glucose, a simple carbohydrate (145147). However, the dietary carbohydrate content does not strongly impact post-prandial blood glucose in cats, except when the diet is directly supplemented with glucose (21, 105).…”
Section: Impact Of Domestication and Captivity On Carnivore Carbohydrmentioning
confidence: 99%
“…In those patients, a diminishing 'early-phase' insulin response is associated with a progressive loss of glycaemic control (Kahn, 2003). With a high dextrose load as used in this study, the early-phase insulin response of cats is found to be diminished with obesity, glucose intolerance, and diabetes (O'Brien et al, 1985;Hoenig et al, 2002).…”
Section: Discussionmentioning
confidence: 83%